Consumer perceptions of brand authenticity: a review of purpose-washing phenomena in branding - Rihhadata Aisy; Mohammad Iqbal; Anni Rahimah (Universitas Negeri Surabaya, Indonesia, 2025)
In recent years, brands have increasingly adopted value-driven marketing strategies by aligning themselves with social causes such as environmental sustainability, gender equality, and other human rights issues. However, many brands have been criticised for engaging in purpose-washing, superficially promoting social values without genuine commitment, threatening consumer trust and perceptions of brand authenticity. This study explores how purpose-washing practices—including greenwashing, femwashing, rainbowwashing, and wokewashing—shape consumer perceptions of brand authenticity. Using a Systematic Literature Review (SLR) approach, this research synthesises findings from articles published between 2020 and 2025. The review identifies key antecedents of authenticity perception, such as message clarity, cause–brand fit, communication strategies, psychological connection, and perceived sincerity. It also maps the theoretical frameworks used such as Attribution Theory, Congruence Theory, and Construal Level Theory and highlights the psychological and behavioural outcomes associated with perceived authenticity, ranging from positive attitudes and loyalty to skepticism, backlash, and brand avoidance. The results indicate that brand authenticity is crucial in influencing how consumers react to value-driven campaigns, and that any misalignment between a brand’s messaging and its actual practices tends to provoke perceptions of hypocrisy. This study concludes that authentic communication and ethical consistency are essential for maintaining trust in brand activism. The research offers practical implications for marketers, emphasising the importance of transparency and long-term alignment with social values. It also provides a foundation for future empirical studies examining the complex relationship between authenticity, ethics, and consumer behaviour in branding.